PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI PERSAMAAN QUADRAT KELAS IX D SMPN 1 TERARA TAHUN PELAJARAN 2019/2020 - Jumuhur, Jumuhur (LEMBAGA PENELITIAN DAN PENDIDIKAN (LPP) ARROSYIDIN, 2023)
Improving Learning Outcomes is a concept of learning activities that assist teachers in carrying out mathematics learning activities on quadratic equation material by trying to maximize the active role of students, especially how students are able to carry out tasks as explained and exemplified by the teacher. With this concept, learning outcomes are expected to be more meaningful for students. The purpose of this classroom action research (CAR) is to find out the increase in Physical Education learning outcomes on quadratic equations in class IX students of SMPN 1 Terara through the STAD method. In class action research (PTK) this was carried out in 2 cycles, from the results of the actions taken it was proven to be able to increase students' learning completeness classically, namely in cycle I the student graduation rate was 50%, which increased to 82.3% in cycle II. The results of this classroom action research show that learning by applying the STAD method can improve mathematics learning outcomes in the quadratic equation material and student learning completeness in mathematics with mastery reaching 82.3% in CYCLE II.